Hot air in Kyoto, cold air in The Hague - Urs Steiner Brandt; Gert Tinggaard Svendsen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2001)
Why did the climate negotiations in The Hague fail? Our contribution is to argue that the conflict between the European Union and the United States stems mainly from disagreement on the cost issue. We argue that three main concerns promoted by the European Union in The Hague, i.e. a 50% national emission ceiling (the supplementarity principle), the use of carbon sinks and an international market control system, can be solved by less restrictions on free GHG trade and by establishing the World Trade Organization as an international authority. Because the US face much higher future reduction costs than the EU, the US will be imposed considerably higher costs than the negotiations in Kyoto were based on. Thus, to make the US stay in an international GHG emission- trading scheme, the EU must reconsider and acknowledge US claims for cheaper reduction options and the right to trade hot air. This point is important. If the US do not participate, the increase in emissions will be much higher than the emission reduction following the EU supplementarity proposal.
Keywords: Q28; H2; H4; 330; Hot Air; Global GHG Trade; Kyoto Protocol; The Hague; National Emission Ceiling; Carbon Sink; Control System; Cost Issue; EU; US.; Internationale Klimapolitik; Klimaschutz